2008
DOI: 10.1002/jat.1408
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of exposure to vapours of standard and dearomatized white spirits in humans. 1. Dose‐finding study

Abstract: A move from 'standard' white spirit (stdWS, 15-20% aromatics) to low-aromatic or dearomatized white spirit (deWS) has been seen, as the latter are considered to carry a smaller risk of health effects. However, data on health risks of deWS on humans are sparse. The aim of this dose-finding study was to identify thresholds of irritation and central nervous system (CNS) effects of the two types of white spirit, as a basis for more detailed studies. Four female and four male healthy volunteers rated symptoms relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…More recently, studies were reported in which the effects of short-term exposure to either "regular white spirits" or "dearomatized white spirits" 40 were compared (Ernstgard et al 2009a(Ernstgard et al , 2009b. In these studies, volunteers were exposed in 10-minute steps to doses that were increased from 0.5-600 mg/ m 3 (0.1 to 109 ppm).…”
Section: Observations Of Acute Cns Effects and Upper Respiratory Tracmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, studies were reported in which the effects of short-term exposure to either "regular white spirits" or "dearomatized white spirits" 40 were compared (Ernstgard et al 2009a(Ernstgard et al , 2009b. In these studies, volunteers were exposed in 10-minute steps to doses that were increased from 0.5-600 mg/ m 3 (0.1 to 109 ppm).…”
Section: Observations Of Acute Cns Effects and Upper Respiratory Tracmentioning
confidence: 99%
“…In these studies, volunteers were exposed in 10-minute steps to doses that were increased from 0.5-600 mg/ m 3 (0.1 to 109 ppm). Effect levels were based on the reports of the volunteers in a range-finding study (Ernstgard et al 2009a), with more objective measures used in a follow-up study in which the volunteers were exposed for 4 h (Ernstgard et al 2009b). The authors reported that in the studies involving short exposure periods, the median levels of irritation were given as "somewhat" for "regular white spirits" and "hardly at all" for the dearomatized white spirit, and ratings of acute CNS effects were "hardly at all".…”
Section: Observations Of Acute Cns Effects and Upper Respiratory Tracmentioning
confidence: 99%
See 3 more Smart Citations